Injury analysis of 257 hospitalized casualties of the Jishishan earthquake in Linxia Prefecture - Xuequan Wei; Mingyan Ma; Zhanlin Zhang; Xiaozhong Li; Xinting Lu; Wenguang Pan; Yongdong An (Frontiers in Public Health)
ObjectiveTo analyze the characteristics of injuries sustained by casualties of the Jishishan earthquake in Jishishan County, Linxia Hui Autonomous Prefecture, Gansu Province, China.MethodsA descriptive research approach was employed. Data were retrospectively collected and analyzed for earthquake-related injuries among patients admitted to the People’s Hospital of Linxia Hui Autonomous Prefecture, the People’s Hospital of Jishishan County, and the Traditional Chinese Medicine Hospital of Linxia Hui Autonomous Prefecture.ResultsA total of 257 patients were hospitalized: 142 at the People’s Hospital of Linxia Hui Autonomous Prefecture, 91 at the People’s Hospital of Jishishan County, and 24 at the Traditional Chinese Medicine Hospital of Linxia Hui Autonomous Prefecture. Most injuries occurred during the main shock (96.5%). In total, 802 injuries were diagnosed, with fractures accounting for 46.6%, followed by visceral injuries (12.0%). The thorax was the most frequently affected site (25.8%), followed by the head (19.5%). Dislocations primarily involved the shoulder-upper arm (50.0%), whereas soft tissue contusions were most common in the lower back (20.3%). Skin lacerations were primarily located on the head (44.7%). Visceral injuries mainly affected the thorax (77.1%), with crush injuries concentrated in the hip-thigh region (38.5%). Hematomas and hemorrhages were predominantly seen in the head (87.0 and 76.0%, respectively). Single fractures were most frequent in the thorax (21.2%) and pelvis (15.2%). Pelvic fractures were the most common single-region multiple fractures (10.5%), whereas thorax+lower back injuries (13.7%) were the most frequent multiple-region fractures. Lung contusions constituted 67.0% of visceral injuries.ConclusionIn the Jishishan earthquake, pelvic and thorax fractures were observed as the main injuries, reflecting the interaction between the vertical collapse mechanism and the vulnerability of the buildings in the earthquake area. This study suggests the need to optimize the allocation of emergency resources for combined thorax-lower back-pelvic injuries in the plateau environment and to enhance the retrofitting of earthquake-resistant buildings in rural areas to reduce the incidence of such injuries. The core findings of this study support empirical evidence for the regional specificity of the earthquake injury spectrum, providing key evidence for regionalized prevention and treatment of earthquake trauma.